A Randomized Trial Comparing Skin Antiseptic Agents at Cesarean Delivery. Issue 6 (June 2016) - Tuuli, Methodius G.; Liu, Jingxia; Stout, Molly J.; Martin, Shannon; Cahill, Alison G.; Odibo, Anthony O.; Colditz, Graham A.; Macones, George A.
Abstract : (Abstracted from N Engl J Med 2016;374:647–655) Cesarean delivery is the most common major surgical procedure among women in the United States. Surgical-site infections complicate 2% to 5% of all surgical procedures and 5% to 12% of cesarean deliveries.